Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Electrochemically regenerable MXene/high-entropy prussian blue analogue cathodes for U(VI) capture in hybrid capacitive deionization - Huan Lu; Jinghao Huang; Jianhong Ma; Dexin Ding; Liangbing Sheng; Yang Ding; Hui Zhang; Feng Li; Yongdong Wang (Journal of Environmental Chemical Engineering, 2026)

Impact of genetic modifications in starch biosynthesis on 3D printing performance of rice starches - Yaqi Hu; Ziliang Qin; Li Ding; Xiaoning Liu; Xingxun Liu; Deyong Zhu; Jacob Judas Kain Kirkensgaard; Tomasz Pawel Czaja; Sheng Chen; Andreas Blennow; Jiyu Yang; Jinsong Bao; et al. (Food Chemistry, 2026)

Dual-functional electrolyte additives enable interfacial stabilization and accelerated sulfur conversion in aqueous Zn-S batteries - Lei Hu; Shuaibo Li; Shihao Wu; Lingli Liu; Yagang Xing; Lili Wang; Tao Ding; Haoran Du; Ningning Zhou; Sheng Liang; Xinling Yu; Xulai Yang (Chemical Engineering Journal, 2026)

Making Waves: Bridging the scale gap in aquatic phosphorus cycling - Hu Sheng; Cai Li; Guoqiang Zhao; Yuanrong Zhu; Jingfu Wang; Huacheng Xu; Shiming Ding (Water Research, 2026)

Capillary-driven microfluidics: Interfacial physics, materials, manufacturing strategies, passive flow-control, and emerging applications - Li Jiang; Fangming Sheng; Weihong Ma; Zhijuan Su; Zhuoqing Yang; Guifu Ding; Faheng Zang (Chemical Engineering Journal, 2026)

Effects of ground motion types and rubber-sand-concrete damping layer on the seismic fragility of tunnel linings - Kaichen Li; Changdong Ding; Xiancheng Mei; Hao Sheng; Zhen Cui; Xuesong Cai; Jiajun Wu; Qian Sheng; Jian Chen (Transportation Geotechnics, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

The impact of aftertreatment technology evolution on greenhouse gas emissions from heavy-duty trucks in China - Hongfei Chen; Rencheng Zhu; Gang Li; Yan Ding; Liang Ji; Junfang Wang; Xuexue Jing; Quankang Han; Fengbin Wang; Tengteng Li; Xianglin Zhong; Sheng Su; et al. (Environmental Pollution, 2026)

Genome-wide interactions with cadmium exposure in dysglycemia: populational effects and molecular insights - Qi Jiang; Bin Li; Yunfei Ma; Wanying Shi; Liang Ding; Naifan Hu; Yunhao Zhao; Yingli Qu; Zheng Li; Peijie Sun; Yifu Lu; Donghui Zhang; et al. (Journal of Hazardous Materials, 2026)

DNA-based one-pot rapid biosensing platform integrating turn-back loop primer-accelerated LAMP and Pyrococcus furiosus Argonaute for meat visual authentication - Sheng Ding; Jing Li; Minglong Yang; Yujia Song; Xiangke Niu; Mei Li; Yao Luo (Journal of Zhejiang University-SCIENCE B, 2026)

Associations of serum per- and polyfluoroalkyl substances (PFAS) mixture with the risk of chronic diseases: evidence from single‑ , multi-pollutant, and machine learning models - Mei Li; Liting Sheng; Zige Ding; Guangsheng Yu; Yichu Chen; Qitian Chen; Wei Shao; Bingxin Liu; Mulong Du; Dongying Gu; Silu Chen; Junyi Xin; et al. (Archives of Toxicology, 2026)

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Labile Fe(III) species control arsenic adsorption and oxidation during magnetite-solution interactions under anoxic conditions - Xinyue Yu; Di Wu; Wan Cheng; Yuefei Ding; Xiaoxu Li; Jing Chen; Xiaohui Wu; Xin Zhang; Juan Liu; Linling Wang; Anxu Sheng; Kevin M. Rosso (Geochimica et Cosmochimica Acta, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Exploring molecular-level rolling friction based on cyclodextrins for lubrication - Jiao Wang; Hao Cao; Wei You; Ding Xiao; Lan Sheng; Yuan Wang; Honggang Mei; Qing Bi; Xuedong Xiao; Yuping Wang; Guangfeng Li; Chenchen Wang; et al. (Carbohydrate Polymers, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Impaired Glymphatic-Meningeal Lymphatic Function in Patients with Spontaneous Subarachnoid Hemorrhage - Jianan Lu; Miao Lin; Heping Tian; Yibo Liu; Bingrui Zhu; Jin Mao; Jiahao Zhang; Haocheng Zhang; Sixuan Tian; Xu Li; Ding Xu; Chenhan Ling; et al. (Translational Stroke Research, 2026)

Plant bioavailable phosphorus content in animal manure- and sewage sludge-based char and ash: Effect of thermal treatment temperature and condition - Xuan Luo; Wei Ding; Adi Radian; Ling Tan; Yukun Sheng; Cheng Li; Zhenyu Wu; Keke Xiao (Waste Management, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Pyrazinamide-induced hepatotoxicity mediated by aldehyde oxidase and xanthine oxidase - Mingyu Zhang; Chunjing Guan; Gaofan Sheng; Zifang Ding; Yanjia Zhao; Guode Zhao; Weiwei Li; Zixia Hu; Ying Peng; Jiang Zheng (Archives of Toxicology, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Hydrogeology of reservoirs for deep geological storage of saline coal mine drainage in groundwater Basin - Song Du; Zhan Yang; Xiao Zhang; Sheng Tao; Xiang Li; Qiaohui Che; Yinglin Fan; Yan Ding; Zhe Jiang; Yanxin Wang (Journal of Hydrology, 2026)

Efficient uranium extraction by a bifunctional MXene: Performance and mechanism in weakly acidic uranium mining wastewater - Liangbing Sheng; Dexin Ding; Hui Zhang; Jianhong Ma; Feng Li; Nan Hu; Weiwen Deng; Yang Chen; Zhengji Yi; Rongying Zeng (Journal of Environmental Chemical Engineering, 2026)

Zinc-iron layered double hydroxide enhances cadmium tolerance in tobacco via cell wall immobilization and regulation of phenylpropanoid and nitrogen metabolism - Xiaoyan Sui; Zhenyu Zhao; Qiang Ma; Zhongqing Liu; Sheng Zhang; Jianbing Ding; Zhengyu Deng; Pengfei Yi; Weijie Yan; Xiaoxuan Yi; Haocun Tang; Zhenhua Wang; et al. (Journal of Environmental Management, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

The Influence of Non-tidal Ocean Loading in the South China Sea on iGrav-048 Superconducting Gravimeter Observations at the Haikou Station - Aobing Zhang; Zhongya Li; Minzhang Hu; Jin Wei; Hongtao Hao; Zhensen Ding; Zhengsong Chen; Jiangang Jia; Sheng Li (Pure and Applied Geophysics, 2026)

A Framework for Extending Rock Strength Criteria to Anisotropy - Huai-Sheng Xu; Shao-Jun Li; Ding-Ping Xu; Min-Zong Zheng; Quan Jiang; Guang-Liang Feng; Liu Liu (Rock Mechanics and Rock Engineering, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Strain Localization and Failure Evolution in Rock–Coal Composites Considering Interaction Mechanisms: A Theoretical and Experimental Investigation - Faxin Li; Qianqian Xue; Zhi Li; Yisong Ding; Jicheng Zhang; Sheng Wang (Rock Mechanics and Rock Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The insect pathogenic fungus Beauveria bassiana excretes a novel effector essential for fungal colonization within the hosts - Kang Wei; Jin-Li Ding; Xue-Ting Wang; Ben-Jie Gao; Ming-Guang Feng; Sheng-Hua Ying (Pesticide Biochemistry and Physiology, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Upwelling enhances cycling and emissions of very short-lived halocarbons: Biogeochemical mechanisms and climate feedbacks - Ya-Wen Zou; Qin-Sheng Wei; Cheng-Xuan Li; Xing Zhai; Ming Xin; Xiao-Meng Duan; Hui Ding; Baodong Wang (Global and Planetary Change, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Clumped isotopes tracing methane cycle and budget: a review - Xinchu Wang; Cong-Qiang Liu; Jiaxu Han; Jiarui Liu; Timothy Csernica; Naizhong Zhang; Hu Ding; Jonathan Gropp; Jennifer McIntosh; Si-Liang Li; Sheng Xu; Rob M. Ellam (Earth-Science Reviews, 2026)

Iron-ceramsite with balanced electron transfer capacity enables simultaneous removal of refractory organics and nitrogen in coking wastewater by single-stage BAF - Hui Zhai; Ding Ma; Jin Wang; Wusong Xu; Yifan Jiang; Bixuan Sheng; Qinglong Guo; Zhiguo Li; Ping Guo; Zhengbo Yue (Chemical Engineering Journal, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

High-resolution spatial mapping of electrocorticographic activities with NeuroCam: a 4096-channel, multiplexed flexible thin-film transistor array - Yang Xie; Zepeng Zhang; Muyang Liu; Jinhong Guo; Miao Xu; Lei Zhou; Lei Zhang; Lihao Yao; Xiaolin Zhou; Zhengwei Hu; Liang Ma; Xiaojian Li; et al. (Science Bulletin, 2025)

Broadband vibration isolation of floating raft system via sandwich metamaterial with acoustic black hole absorbers - Siting Hao; Hui Sheng; Haiqin Li; Zhiyong Zhang; Qian Ding (Ocean Engineering, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

A review of dissolved inorganic carbon isotopic fractionations in carbonate-bearing areas: Processes, models and applications - Jun Zhong; Hu Ding; Gibran Romero-Mujalli; Albert Galy; Sheng Xu; Cong-Qiang Liu; Si-Liang Li (Earth-Science Reviews, 2025)

Defect-mediated dual role interfaces enables the sulfur reduction reaction kinetics for highly stable lithium sulfur batteries - Xinmeng Li; Jiafeng Zhu; Rui Sheng; Tianmei Xu; Kai Chen; Juan Ding; Yudai Huang (Chemical Engineering Journal, 2025)

Comparative analysis of supplemental irrigation effects on structure and digestion of normal and amylose-only barley starches - Wenxin Liang; Klaus Herburger; Ke Guo; Jacob Judas Kain Kirkensgaard; Kim Henrik Hebelstrup; Staffan Persson; Sheng Chen; Yuyue Zhong; Andreas Blennow; Li Ding (Carbohydrate Polymers, 2025)

Characterizing maize starch gelatinization by Low-Field NMR spectroscopy - Li Ding; Samira Ebrahimi; Xingxun Liu; Staffan Persson; Jacob Judas Kain Kirkensgaard; Kasper Enemark-Rasmusse; Jinhui Chang; Sheng Chen; Andreas Blennow; Tomasz Pawel Czaja; Yuyue Zhong (Carbohydrate Polymers, 2025)

Asthenospheric upwelling-induced seismic activity in the eastern North China Craton: Evidence from viscosity obtained from an MT study - Baochun Li; Gaofeng Ye; Sheng Jin; Wenbo Wei; Letian Zhang; Hao Dong; Chengliang Xie; Yaotian Yin; Shaohuai Sun; Zhaoyuan Kang; Peng Ding; Yiwu Zhang; et al. (Tectonophysics, 2025)

The response characteristics of fault-crossing tunnel subjected to different sequential combination actions of strike-slip fault dislocation and seismic wave propagation - Xiancheng Mei; Changdong Ding; Jianhe Li; Bo Lou; Zhen Cui; Mingnan Xu; Qian Sheng; Yajie Song; Jian Chen (Soil Dynamics and Earthquake Engineering, 2025)

Deep-sea ventilation shifts and glacial climate evolution: redox history of the central Philippine Sea over 6.7 Myr - Liang Yi; Yibing Li; Sheng Xu; Bangqi Hu; Martín Medina-Elizalde; Xue Ding; Yeqiang Shu; Pavel Mikhailik; Panfeng Li; Congxi Fang; Yonghang Xu; Haifeng Wang; et al. (Quaternary Science Reviews, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Microbial community dynamics and ecological interactions during an atypical winter Cerataulina pelagica (Bacillariophyta) bloom in Laizhou Bay, southern Bohai Sea - Long Yang; Hongwei Wang; Zhengguo Cui; Hualong Wang; Xiaokun Ding; Di Zhang; Huanyu Zhang; Sheng Li; Tao Jiang (Marine Environmental Research, 2025)

Recent progress in DNA-based approaches for authenticating herbal materials and botanical dietary supplements - Rong Chen; Wenjun Song; Hongling Chen; Tongyi Peng; Huilin Li; Sheng Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Multiscale structural design of heterostructured carbon/boron nitride aerogels for efficient thermal conductivity and broadband electromagnetic wave absorption - Zhengxuan Li; Wang Yang; Chen Zhang; Zhongzhen Ding; Shaoxiong Du; Xi Wu; Junyan Dong; Wenjie Zhu; Sheng Liu; Yu Lin; Lei Liu; Yongfeng Li (Chemical Engineering Journal, 2025)

Flexible and ultra-high electromagnetic interference shielding films with fiber-bridged segregated conductive network - Jia-Le Zhang; Sheng Yong; Tong Wang; Jie Feng; Jie Li; Yue-Yi Wang; Ling Xu; Gan-Ji Zhong; Jun Lei; Ding-Xiang Yan; Zhong-Ming Li (Chemical Engineering Journal, 2025)

Sub-meter resolution wetland map of Hainan with detailed types from multi-source satellite imagery - Xiaohai Zhang; Jiahui Liu; Sheng Liu; Jiaju Yu; Kang Deng; Weiping Ding; Zeheng Chen; Fangyi Li (Frontiers in Marine Science, 2025)
Introduction Obtaining wetland data with high spatial accuracy and typological completeness is essential for understanding ecosystem functions, evaluating services, and informing conservation policy. However, fine-scale wetland mapping in tropical island regions remains challenging due to persistent cloud cover, image limitations, complex wetland types, and dynamic hydrology. Methods We developed a sub-meter resolution wetland mapping framework for Hainan Island, China, by integrating multi-source optical imagery (WorldView-2/3, Gaofen-1/2), dual-temporal features, and RTK-based field validation. A hierarchical classification system was designed, consisting of three major categories and 17 subcategories, aligned with Ramsar Convention criteria and adapted to island-specific conditions. Results The 2019 wetland map (3842.84 km 2 ) achieved an overall accuracy of 96.13% (Kappa = 0.95). The framework successfully identified numerous small and fragmented wetland patches (0.0004–0.08 km 2 ) that had been omitted in national wetland inventories. The results also revealed rapid artificial wetland expansion and pronounced spatial heterogeneity in natural wetlands. Discussion This study delivers a reliable high-resolution dataset and a replicable methodology for tropical island wetland mapping. The results provide a critical basis for wetland monitoring, blue carbon assessment, and ecological management, while offering a transferable framework that can be applied to other coastal and island environments.

Impacts of particle size distribution on the permeability of hydrate-bearing sediments using a DEM-PNM approach - Guangyao Li; Yanlu Ding; Haitao Zhang; Sheng Dai (Computers and Geotechnics, 2025)

Characterization of different high amylose starch granules. Part III: How starch fine structures affect retrogradation and formation of type 3 resistant starch - Li Ding; Jiyu Yang; Jacob Judas Kain Kirkensgaard; Kasper Enemark-Rasmussen; Jinhui Chang; Lude Zhang; Sheng Chen; Andreas Blennow; Yuyue Zhong (Carbohydrate Polymers, 2025)

Biotransformation: a novel approach for the production of 6-hydroxyluteolin 7- O -methylglucuronide compound with antioxidant and anti-inflammatory potential - Chien-Yu Wu; Muddasir Khan; Hsiou-Yu Ding; Tzi-Yuan Wang; Yi-Xuan Li; Chun-Wei Liu; Jiumn-Yih Wu; Te-Sheng Chang (Natural Product Research, 2025)

Enhanced deep denitrification for high-salinity wastewater treatment by constructing biofilm-based technology - Kun Ding; Shan Yang; Hao Hu; Zhenghao Li; Haoran Duan; Xiaoqiang Chen; Yankun Liu; Guoping Sheng (Journal of Environmental Management, 2025)

Responses of Subsoil Organic Carbon to Climate Warming and Cooling Is Determined by Microbial Community Rather Than Its Molecular Composition - Yuzhang Li; Yao Wei; Lile He; Bo Fan; Kunhe Liu; Mingli Ding; Yigang Hu; Xin Jing; Biao Zhu; Shiping Wang; Jin‐Sheng He; Xinquan Zhao; et al. (Ecology Letters, 2025)
Little is currently known about how long‐term climate changes modulate the relationship between soil organic carbon (SOC) molecular composition, microbial community and SOC storage and the mechanisms involved. Here, we show substantial changes in subsoil SOC in the Qinghai‐Tibetan alpine grasslands over 16 years of soil warming and cooling. Warming reduced SOC content by 8.5%, whereas cooling increased it by 7.0%. Neither warming nor cooling affected plant‐ and microbial‐derived molecular components. However, warming elevated the fungal‐to‐bacterial biomass ratio (F/B) and the gram‐positive to gram‐negative bacterial biomass ratio (G+/G‐) by 15.0% and 8.6%, respectively, whereas cooling reduced them by 4.5% and 9.6%. Warming reduced SOC storage by directly increasing F/B and G+/G‐ and indirectly decreasing the soil carbon‐to‐nitrogen ratio, whereas cooling enhanced SOC storage primarily by decreasing F/B. Conventional warming experiments, which consider only climate warming and neglect cooling, may underestimate the negative impacts of warming on subsoil SOC pools in alpine grasslands.

Ginsenoside Rb1 combined with Lycium barbarum polysaccharide alleviate the Tripterygium wilfordii polyglycoside-induced oligoasthenozoospermia in mice by inhibiting ZnT3-mediated oxidative stress response - Xianrui Li; Jin Ding; Jingshang Wang; Junqin He; Wen Sheng (Journal of Trace Elements in Medicine and Biology, 2025)

Study of the pore structure and fractal characteristics of mixed-sediments reservoirs based on low-temperature gas adsorption and high-pressure mercury injection - Fengjuan Dong; Chao Zhou; Jiayi Zhou; Xiaojun Ding; Jun Sheng; Kunkun Li; Dazhong Ren; Xuefei Lu (Carbonates and Evaporites, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

High levels of fishmeal replacement with torula yeast reduces growth, negatively affects hepatic and intestinal health, and intestinal microbiota of largemouth bass (Micropterus salmoides) - Ze Sheng Zhang; Zhi Li Ding; Meng Ting Wang; Dong Chun Li; Wen Qi Chen; Shun Yang; Hui Fei (Aquaculture, 2025)

Follicle mural granulosa cells encapsulated in sodium alginate gel improve developmental competence of porcine oocytes of in vitro maturation - Qi Zhang; Yongfeng Zhou; Ran Ding; Qi Li; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2025)

The genomic characteristics of dominant Salmonella enterica serovars from retail pork in Sichuan province, China - Lanqi Li; Honghu Sun; Jianyun Zhao; Huanjing Sheng; Menghan Li; Lanxin Zhao; Shiwei Liu; Séamus Fanning; Lu Wang; Yang Wang; Yongning Wu; Hao Ding; et al. (International Journal of Food Microbiology, 2025)

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Carbon dioxide–induced acidification enhances short‐lived brominated hydrocarbons production in oligotrophic oceans - Ya‐Wen Zou; Cheng‐Xuan Li; Qin‐Sheng Wei; Qian‐Yao Ma; Hui Ding; Xiao Meng Duan; Xing Zhai; Bao‐Dong Wang (Limnology and Oceanography, 2025)
Oceanic emission is a primary source of brominated very short‐lived substances (BrVSLs) to the atmosphere, which have important effects on stratospheric ozone chemistry. Marine biogeochemical processes regulating BrVSLs are often sensitive to ocean acidification. Yet, the response of BrVSLs production to acidification remains poorly understood. Herein, the effects of acidification on the production of two main BrVSLs, dibromomethane (CH 2 Br 2 ) and tribromomethane (CHBr 3 ), were studied by ship‐based incubation experiments at three stations in the South Atlantic and Indian Oceans. The average CH 2 Br 2 and CHBr 3 concentrations increased by 17.2–58.7% and 14.3–80.3% due to acidification under the in situ nutrient conditions with nutrient and/or iron limitation at the three stations, but the mechanisms driving these increases varied among different regions. The increased bromoperoxidase (BrPO) activity caused by acidification facilitated BrVSLs release in the Eastern Tropical Indian Ocean, where diatoms were dominant. CHBr 3 increased due to acidification as a result of enhanced reactivity of dissolved organic matter (DOM) in the Eastern Tropical Atlantic, where dinoflagellates were dominant. Brominated very short‐lived substances increased due to acidification as a result of a combined effect of the above two mechanisms in the Benguela Current Coastal with high phytoplankton abundance. Under the nutrient and/or iron addition conditions with nutrient and iron sufficiency, however, acidification did not promote BrVSLs production due to its only minor effect on the BrPO activity and reactivity of DOM, partly because the effect of increased oxidative stress was offset by that of changed phytoplankton composition. Our study provided a basis for future modeling on the impact of acidification on global BrVSLs emissions.

Mechanism of Lung Fibrosis Caused by Rare Earth Samarium Oxide Through Hippo Signaling Pathway and the Intervention of GBE - Ruixia Ding; Ying Sun; Teng Ma; Haijing Yin; Yannan Bi; Sheng Li; Li Wang; Xiaohui Wang (Biological Trace Element Research, 2025)

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

A family of nitronate monooxygenase-domain proteins are essential for biocontrol potential of the insect mycopathogen Beauveria bassiana - Hao Zhang; Xin-Yi Wang; Ting-Fei Sun; Tian-Jing Chen; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Pesticide Biochemistry and Physiology, 2025)

Overlooked importance: The supporting roles of satellite wetlands for waterbirds around the Yangtze-connected lakes, China - Guangyao Wang; Chengrong Pan; Shilong Yu; Sheng Xu; Shuheng Dai; Jingjing Ding; Xiangrong Song; Chunlin Li; Yong Zhang; Willem F. de Boer (Journal of Environmental Management, 2025)

Advanced micro-textural engineering for the fabrication of high-performance superomniphobic surfaces - Chang Lv; Tao Wang; Yuanwei Ding; Haiyan Li; Yulong Ying; Lvlv Ji; Weihao Cui; Lei Liu; Sheng Wang (Chemical Engineering Journal, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Application of two crucial hemicellulolytic enzymes in fish diet: Xylanase and mannanase - Xiao yan Wang; Zhi li Ding; Ze sheng Zhang; Chen bin Zhu; Shun Yang; Hui Fei (Animal Feed Science and Technology, 2025)

The influence of steep faults at various avoidance distances on the stability of hard rock caverns: Physical model experiments and DEM simulations - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Shi-jie Chen; Guang-liang Feng; Quan Jiang; Xin-hao Zhu; Shu-qian Duan (Tunnelling and Underground Space Technology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Solving the temporal lags in local significant wave height prediction with a new VMD-LSTM model - Shaotong Zhang; Zixi Zhao; Jinran Wu; Yao Jin; Dong-Sheng Jeng; Sanzhong Li; Guangxue Li; Dong Ding (Ocean Engineering, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Enhanced thermochemical heat storage performance of CaO/CaCO3 via pyroligneous acid impregnation and Co/Mn co-doping - Zhu-yu Li; Le-ran Li; Sheng Li; Ding-can Wang; Qi Niu; Kai Li; Ji Liu; Qiang Lu (Chemical Engineering Journal, 2024)

Predominant biogenic contribution of dissolved inorganic carbon in karst rivers, Southwest China - Yue Zheng; Hu Ding; Jun Zhong; Yunchao Lang; Si-Liang Li; Sheng Xu; Cong-Qiang Liu (Chemical Geology, 2024)

Exploring secretory signal sequences useful in excreting recombinant proteins in Beauveria bassiana as biocontrol fungus - Kang Wei; Jin-Li Ding; Hang-Rong Xu; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2024)

Regulation of ferrihydrite biotransformation by Fe(II) supply rates and extracellular polymeric substances - Anxu Sheng; Yurong Deng; Yuefei Ding; Linxin Cheng; Yuyan Liu; Xiaoxu Li; Yuji Arai; Juan Liu (Geochimica et Cosmochimica Acta, 2024)

High mobility emissive BN-Embedded Dinaphthalenyl anthracene for organic light emitting transistors - Ze-Wei Lin; Pu Wang; Sheng-Hong Zhao; Yun-Tao Ding; Huanli Dong; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Essential role of composting industry in achieving China’s dual-carbon goals: Case studies from Chinese composting companies - Sheng Hang; Yue Wang; Yuquan Wei; Bo Wang; Bihui Peng; Ziyi Hao; Lei Wu; Longli Zhang; Guochun Ding; Ji Li (Bioresource Technology, 2024)

Unravelling ice growth characteristics beneath cloud tops with joint analysis of airborne Ka-band radar and Himawari observations - Shuangzhi You; Delong Zhao; Haoran Li; Wei Zhou; Yuanmou Du; Ping Tian; Jiujiang Sheng; Wei Xiao; Fei Wang; Hui He; Mengyu Huang; Deping Ding; et al. (Atmospheric Research, 2024)

Label-free SELEX of aptamers for ultra-sensitive electrochemical aptasensor detection of amanitin in wild mushrooms - Renxiang Yang; Changsong Zhao; Sheng Ding; Jia Ruan; Dongqiu Li; Yijia Xiang; Jie Zhou; Huilan Su; Na Li (Analytica Chimica Acta, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Modulating charge distribution of MIL@CuFe-Se by in-situ interface engineering for high performance supercapacitors - Ziyun Zhang; Lei Li; Xiaomin Chen; Wentao Ding; Sheng Han; Jibo Jiang (Chemical Engineering Journal, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Ultrafast DNA detection based on turn-back loop primer-accelerated LAMP (TLAMP) - Jinyi Shi; Sheng Ding; Chen Li; Gangyi Chen; Feng Du; Sifan Wang; Aiqin Yue; Kaiyuan Ren; Zhirong Yang; Pei Xu; Juan Dong; Jinzhong Zhao; et al. (Analytica Chimica Acta, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Comparative Transcriptomics of the Entomopathogenic Fungus Beauveria bassiana Grown on Aerial Surface and in Liquid Environment - Kang Wei; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Current Microbiology, 2024)

Perturbation algorithm for refueling reactivity coefficient in the pebble-bed high temperature reactor - Zhongkai Sheng; Bing Xia; Ding She; Fu Li; Zuoyi Zhang (Annals of Nuclear Energy, 2024)

A semi-analytical wavelet finite element method for wave propagation in rectangular rods - Wenxiang Ding; Liangtian Li; Hongmei Zhong; Ying Li; Danyang Bao; Sheng Wei; Wenbin Wang (Wave Motion, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Severe flood modulates the sources and age of dissolved organic carbon in the Yangtze River Estuary - Zhao Liang Chen; Yuanbi Yi; Wenjing Fu; Wenzhao Liang; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; Ding He (Environmental Research, 2024)

Estimating the Mechanical Properties of Rocks and Rock Masses Based on Mineral Micromechanics Testing - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shu-qian Duan; Huai-sheng Xu; Quan Jiang; Shi-li Qiu (Rock Mechanics and Rock Engineering, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

A study on an accurate modeling for distinguishing nitrogen, phosphorous and potassium status in summer maize using in situ canopy hyperspectral data - Di Lin; Yue Chen; Yongliang Qiao; Ding Qin; Yuhong Miao; Kai Sheng; Lantao Li; Yilun Wang (Computers and Electronics in Agriculture, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Targeting the undruggables—the power of protein degraders - Chao Zhang; Yongbo Liu; Guangchen Li; Zhouli Yang; Chi Han; Xiuyun Sun; Chunquan Sheng; Ke Ding; Yu Rao (Science Bulletin, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

H2S Regulates the Phenotypic Transformation of Astrocytes Following Cerebral Ischemia/Reperfusion via Inhibiting the RhoA/ROCK Pathway - Yanyu Ding; Fang Fang; Xiaolong Liu; Shuyan Sheng; Xueyan Li; Xiaojiao Yin; Zhiwu Chen; Jiyue Wen (Molecular Neurobiology, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Rhombohedral platinum-copper intermetallic compound: A high phosphate tolerance electrocatalyst for HT-PEMFC - Wenrui Zhang; Sheng Xu; Yunxu Yang; Qingwei Gao; Sheng Zhu; Kun Ding; Qiaoxia Li; Penghui Shi; Yulin Min (Chemical Engineering Journal, 2024)

Integrated microbiome and metabolome analyses reveal the effects of low pH on intestinal health and homeostasis of crayfish (Procambarus clarkii) - Zhanqi Wang; Jiapeng Li; Pengfei Zhao; Zaihang Yu; Lianlian Yang; Xueyan Ding; He Lv; ShaoKui Yi; Qiang Sheng; Liqin Zhang; Fan Zhou; Hua Wang (Aquatic Toxicology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Safe and environmentally friendly use of coal gangue in C30 concrete - Chao-qiang Wang; Ding-yi Duan; Xin Li; Dong-sheng Bai (Sustainable Chemistry and Pharmacy, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Microplastics as emerging contaminants in textile dyeing sludge: Their impacts on co-combustion/pyrolysis products, residual metals, and temperature dependency of emissions - Ziyi Ding; Weijie Li; Zhibin Chen; Li Wang; Shenzheng Huang; Fatih Evrendilek; Chunxiao Yang; Haiming Cai; Sheng Zhong; Zuoyi Yang; Jingyong Liu (Journal of Hazardous Materials, 2024)

Biological activities and mass fragmentation pathways of meroterpenoid cochlioquinones from plant pathogenic fungus Bipolaris sorokiniana - Qi Li; Jian-zi Liu; Jian Yang; Yan-duo Wang; Sheng-Xiang Yang; Shu-bin Niu; Gang Ding (Food Chemistry, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Experimental Investigation on the Motion Characteristics of Air-Floating Tripod Bucket Foundation during Free Floating - Xianqing Liu; Yu Ding; Wenlong Li; Puyang Zhang; Kui Yu; Yutao Feng; Nan Lv; Sheng Luo (Journal of Marine Science and Engineering, 2024)
In recent years, multi-bucket foundations have been studied and gradually adopted in engineering practices as a novel foundation for offshore wind turbines within a range of water depth of 30 to 50 m. This study investigated the motion characteristics of air-floating tripod bucket foundation (AFTBF) through a series of experiments during free air-floating. The experimental results show that the surge force appears to be the most important factor influencing pitch moment and motion, whether it is a change in water depth or a draft for AFTBF. The maximum amplitudes of surge acceleration and pitch angle show a trend of increasing with narrower spacing and decreasing with wider spacing, while the heave acceleration shows an opposite trend. The added mass and damping of heave motion for AFTBF increase with shallower water due to the increasing pressure difference between the inside and bottom of bucket foundation. The shallower the water depth and the larger the draft, the longer the resonance period of heave.

Efficient breeding and growth advantage of all-male population in Lanzhou catfish (Silurus lanzhouensis) - Jun-Sheng Niu; Tao Wang; Zhi Li; Zhong-Wei Wang; Miao Ding; Ming-Tao Wang; Zong-Qiang Lian; Jie Mei; Yang Wang; Li Zhou; Xiao-Juan Zhang; Jian-Fang Gui; et al. (Aquaculture, 2024)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Understanding unsaturated sulfate saline soil in cold regions: A comprehensive hydraulic–thermal–air–salt–mechanical model with experimental research - Hongbo Li; Sheng Li; Xinrui Kang; Libo Wu; Yongfa Ding (Cold Regions Science and Technology, 2023)

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Correction to: Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2023)

Carbon mineralization and abiotic methane synthesis within fluid inclusions in mafic minerals from postcollisional pyroxenite - Long Zhang; Qiang Wang; Haiyang Xian; Jin-Sheng Zhou; Xing Ding; Wan-Cai Li (Geochimica et Cosmochimica Acta, 2023)

Tree-inspired and scalable high thermal conductivity ethylene–vinyl acetate copolymer/expanded graphite/paraffin wax phase change composites for efficient thermal management - Xinpeng Hu; Xianrong Huang; Bingqing Quan; Chuanbiao Zhu; Youqiang Yang; Mengjie Sheng; Chao Ding; Haoye Wen; Xiaolong Li; Jingang Wei; Hao Wu; Xiang Lu; et al. (Chemical Engineering Journal, 2023)

Changes in the hydrological and sediment regimes of two neighboring catchments in the past sixty years - Yinjun Zhao; Sheng Wang; Jiaxu Li; Aizhong Ding; Yongping Wei (CATENA, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

One new elemane sesquiterpenoid glycoside and five glycoglycerolipids from Pittosporum truncatum with anti-bacterial activity - Rong Huang; Ji-Li Deng; Sheng-Nan Guan; Jia-Qi Ding; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Insights into the interfacial structure of Cu/ZrO2 catalysts for methanol synthesis from CO2 hydrogenation: Effects of Cu-supported nano-ZrO2 inverse interface - Yangzhi Xu; Maolin Wang; Zhiwei Xie; Dong Tian; Guan Sheng; Xin Tang; Haibo Li; Yichao Wu; Chuqiao Song; Xiaofeng Gao; Siyu Yao; Ding Ma; et al. (Chemical Engineering Journal, 2023)

Synergistic effect of high-valent cobalt oxo species and piezoelectricity on enhanced peroxymonosulfate activation for atrazine removal - Sheng Xiong; Hao Zeng; Rongdi Tang; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chunxia Ding; Daoxin Gong; Yaocheng Deng (Chemical Engineering Journal, 2023)

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Graphene/carbon fiber network constructed by co-carbonization strategy for functional integrated polyimide composites with enhanced electromagnetic shielding and thermal conductive properties - Xiong Li; Tongle Xu; Wenjing Cao; Menghuan Wang; Fengqing Chen; Liyuan Jin; Na Song; Sheng Sun; Peng Ding (Chemical Engineering Journal, 2023)

RNAi-mediated knockdown of the mandibular organ-inhibiting hormone (MOIH) gene stimulates vitellogenesis in the Chinese mitten crab Eriocheir sinensis - Shuquan Ding; Mengting Huang; Na Sheng; Tiantian Chen; Ruihan Xu; Zhaoyuan Luo; Xiuqin Huang; Zhicheng Wan; Shiping Su; Xilei Li (Fisheries Science, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Deciphering roles of microbiota in arsenic biotransformation from the earthworm gut and skin - Hong-Tao Wang; Zong-Zheng Liang; Jing Ding; Gang Li; Sheng-Lei Fu; Dong Zhu (Journal of Hazardous Materials, 2023)

Source characterization of volatile organic compounds in urban Beijing and its links to secondary organic aerosol formation - Quan Liu; Jiujiang Sheng; Yangzhou Wu; Zhiqiang Ma; Junying Sun; Ping Tian; Delong Zhao; Xia Li; Kang Hu; Siyuan Li; Xiaojing Shen; Yangmei Zhang; et al. (Science of The Total Environment, 2023)

Polyketides with antimicrobial activities from Penicillium canescens DJJ-1 - Jia-Peng Wang; Yan Shu; Sheng-Qi Zhang; Lin-Lin Yao; Bing-Xian Li; Li Zhu; Xiao Zhang; Huai Xiao; Le Cai; Zhong-Tao Ding (Phytochemistry, 2023)

Integrating transcriptomic and metabolomic analysis to understand muscle qualities of red swamp crayfish (Procambarus clarkii) under transport stress - Gangpeng Shi; Tianqi Gao; Xuehong Li; Liu Shi; Sheng Chen; Anzi Ding; Xin Li; Yu Qiao; Li Liao; Guangquan Xiong; Lan Wang; Wenjin Wu (Food Research International, 2023)

Seismic performance of squat UHPC shear walls subjected to high-compression shear combined cyclic load - Yue-Yi Li; Jian-Guo Nie; Ran Ding; Jian-Sheng Fan (Engineering Structures, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

The Impact of an Abnormal Zonal Vertical Circulation in Autumn of Super El Niño Years on Non-tropical-cyclone Heavy Rainfall over Hainan Island - Fei Wang; Lifang Sheng; Xiadong An; Haixia Zhou; Yingying Zhang; Xiaodong Li; Yigeng Ding; Jing Yang (Advances in Atmospheric Sciences, 2022)

Physical Model Experimental Study on the Coalface Overburden Movement Law on the End Slope of an Open-Pit Mine - Xinpin Ding; Fengming Li; Zhenwei Wang; Sheng Sang; Mingming Cao (Geotechnical and Geological Engineering, 2022)
Due to technological and safety limitations, there are considerable amounts of coal resources pressed under end slopes in open-pit coal mines. In recent years, this problem has gradually attracted the attention of researchers. How to realize the efficient recovery of side overburden resources while ensuring the stability and safety of slopes has become an important topic for the development of mining technology in China. A 2D/3D integrated simulation experimental device for end slope coal mining is developed. Based on the geological engineering conditions of the Ordos mining area in China, a typical geological engineering model of a near-horizontal slope condition is constructed to simulate the whole process of “roadway group formation—supporting coal pillar failure—slope rock mass instability”. By tracking and monitoring the movement and failure processes of slope rock masses in an end-slope mining field, the yield failure characteristics of coal pillars and the movement and deformation laws of slope rock masses are revealed, and the deformation and failure zoning method of overburden rock in an end-slope mining field is proposed; in addition, the key stages, trigger conditions and key positions of slope deformation and instability are defined. The results show that under the coupling action of the “slope stress field” and “roadway group stress field”, the actual stress of a supporting coal pillar in the deep part of a geometric centre along the slope of a roadway group is greater than the ultimate stress, and then large discontinuous deformations of multiple adjacent coal pillars around the central coal pillar are caused by compressive shear failure, which is the triggering condition of deformation and instability around the mining slope. The key position of yield failure of the supporting coal pillar is located in the deep part of the geometric centre along the slope of the roadway group. At the end of the mining adit, the supporting coal pillar within a width of 2.5–3 times the mining adit will not be destroyed. The boundary of the final collapse plane range of the roadway group is approximately a closed curve formed by two paraboloids, which are axisymmetric with the central pillar and open oppositely; the parabola opening in the shallow part of the slope area is small, and the parabola opening in the deep part of the slope area is large. There is a significant space–time correspondence between the failure of supporting coal pillars and the deformation of the slope surface. According to the failure process of the rock mass structure and the movement and deformation characteristics of the slope surface, the slope after failure can be divided into three areas, and the upper part of the slope is the key area of deformation and instability of the overlying rock mass in the end-slope mining field. These research results provide a theoretical basis for the scientific monitoring and stability control of slopes in an end-slope mining field.

Functional characterization of two homologs of yeast acetyl-coenzyme A synthetase in the entomopathogenic fungus Beauveria bassiana - Jia-Hui Lei; Hai-Yan Lin; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Insight into how fertilization strategies increase quality of grape (Kyoho) and shift microbial community - Xunan Li; Changbin Chu; Sheng Ding; Huawei Wei; Shuhang Wu; Bing Xie (Environmental Science and Pollution Research, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

Two new isoquinoline alkaloids from the seeds of Nandina domestica - Juan Qin; Sheng-Yuan Zhang; Yu-Bo Zhang; Li-Feng Chen; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2021)

Model on Improved Variable Weight-Matter Element Theory for Risk Assessment of Water Inrush in Karst Tunnels - Sheng Wang; Liping Li; Shuai Cheng; Zhenhua Liu; Ruosong Ding; Qiang You (Geotechnical and Geological Engineering, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Two new lignans from Gymnotheca involucrata - Shi-Ji Xiao; Mao-Sheng Zhang; Fang Chen; Li-Sheng Ding; Yan Zhou (Natural Product Research, 2020)

Mbp1, a component of the MluI cell cycle box‐binding complex, contributes to morphological transition and virulence in the filamentous entomopathogenic fungus Beauveria bassiana - Jin‐Li Ding; Hai‐Yan Lin; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2020)
Summary The Mbp1 protein functions as a DNA‐binding protein in the MluI cell cycle box‐binding complex and plays significant roles in yeast development. In this study, an ortholog of yeast Mbp1, BbMbp1, was characterized in a filamentous insect mycopathogen, Beauveria bassiana . BbMbp1 plays an important role in morphological changes under aerial and liquid environments. On the aerial surface, BbMbp1 was indispensable for the biogenesis of conidiophores and conidiation. Under submerged conditions, the ∆ BbMbp1 mutant displayed abnormal spore‐producing structures, with a dramatic decrease in blastospore yield (~95%). The virulence of the ∆ BbMbp1 mutant was notably weakened, which might be due to the defect in in vivo blastospore formation in the insect. Moreover, disruption of BbMbp1 resulted in a substantial reduction in hyphal growth on cadavers. Comparative transcriptomics revealed that BbMbp1 mediated different transcriptomes during the formation processes of conidia and blastospores. Yeast one‐hybrid assays demonstrated that BbMbp1 was required for transcriptional control of a cell wall protein gene, BbCwp , and an integral membrane protein gene, BbImp that played significant roles in conidiation and blastospore formation respectively. Our results demonstrate that BbMbp1 contributes to the morphological transitions in the pathogenic and saprophytic growth of B . bassiana via different genetic pathways.

A new pregnane steroid from cultures of Aspergillus versicolor - Jian-Hai Ding; Zhang-Gui Ding; Jiang-Yuan Zhao; Ming-Gang Li; Dong-Bao Hu; Xian-Jun Jiang; Dong-Sheng Zhou; Fei Wang; Meng-Liang Wen (Natural Product Research, 2019)

δ-Opioid Receptor Activation Attenuates the Oligomer Formation Induced by Hypoxia and/or α-Synuclein Overexpression/Mutation Through Dual Signaling Pathways - Tao Chen; Qinyu Wang; Dongman Chao; Terry C. Xia; Shiying Sheng; Zhuo-Ri Li; Jian-Nong Zhao; Guo-Qiang Wen; Guanghong Ding; Ying Xia (Molecular Neurobiology, 2019)

Roles of hyaluronan in cardiovascular and nervous system disorders - Hong-yan Ding; Ya-nan Xie; Qiang Dong; Koji Kimata; Yoshihiro Nishida; Naoki Ishiguro; Li-sheng Zhuo (Journal of Zhejiang University-SCIENCE B, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

Mechanism underlying the retarded nuclear translocation of androgen receptor splice variants - Ye Liu; Yinyu Wang; Fangfang Wang; Jiexue Pan; Jingjing Xu; Jingyi Li; Chengliang Zhou; Guolian Ding; Yanting Wu; Xinmei Liu; Jianzhong Sheng; Hefeng Huang (Science China Life Sciences, 2019)

Developmental toxicity and apoptosis in zebrafish embryos induced by low-dose γ-ray irradiation - Weichao Zhao; Nan Hu; Dexin Ding; Dingxin Long; Sheng Li; Guangyue Li; Hui Zhang (Environmental Science and Pollution Research, 2019)

A combination of follicle stimulating hormone, estradiol and age is associated with the pregnancy outcome for women undergoing assisted reproduction: a retrospective cohort analysis - Ziru Jiang; Li Jin; Weihui Shi; Ji Xi; Yulian Hu; Xinmei Liu; Jianzhong Sheng; Guolian Ding; Hefeng Huang (Science China Life Sciences, 2019)

Autophagy‐related gene BbATG11 is indispensable for pexophagy and mitophagy, and contributes to stress response, conidiation and virulence in the insect mycopathogen Beauveria bassiana - Jin‐Li Ding; Yue‐Jin Peng; Xin‐Ling Chu; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2018)
Summary Autophagy is a conserved degradation system in eukaryotic cells that includes non‐selective and selective processes. Selective autophagy functions as a selective degradation mechanism for specific substrates in which autophagy‐related protein 11 (ATG11) acts as an essential scaffold protein. In B. bassiana , there is a unique ATG11 family protein, which is designated as BbATG11 . Disruption of BbATG11 resulted in significantly reduced conidial germination under starvation stress. The mutant Δ BbATG11 displayed enhanced sensitivity to oxidative stress and impaired asexual reproduction. The conidial yield was reduced by approximately 75%, and this defective phenotype could be repressed by increasing exogenous nutrients. The virulence of the Δ BbATG11 mutant strain was significantly impaired as indicated in topical and intra‐hemocoel injection bioassays, with a greater reduction in topical infection. Notably, BbATG11 was involved in pexophagy and mitophagy, but these two autophagic processes appeared in different fungal physiological aspects. Both pexophagy and mitophagy were associated with nutrient shift, starvation stress and growth in the host hemocoel, but only pexophagy appeared in both oxidation‐stressed cells and aerial mycelia. This study highlights that BbATG11 mediates pexophagy and mitophagy in B. bassiana and links selective autophagy to the fungal stress response, conidiation and virulence.

Genetic parameters and response to selection for body weight in turbot (Scophthalmus maximus, Linnaeus) - Ding Lyu; Weiji Wang; Sheng Luan; Yulong Hu; Jiantao Guan; Zhixiang Li; Huanhuan Wu; Jie Kong; Shoutang Liu (Acta Oceanologica Sinica, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Transcriptomic insights into the alternative splicing‐mediated adaptation of the entomopathogenic fungus Beauveria bassiana to host niches: autophagy‐related gene 8 as an example - Wei‐Xia Dong; Jin‐Li Ding; Yang Gao; Yue‐Jin Peng; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2017)
Summary Alternative splicing (AS) regulates various biological processes in fungi by extending the cellular proteome. However, comprehensive studies investigating AS in entomopathogenic fungi are lacking. Based on transcriptome data obtained via dual RNA‐seq, the first overview of AS events was developed for Beauveria bassiana growing in an insect haemocoel. The AS was demonstrated for 556 of 8840 expressed genes, accounting for 5.4% of the total genes in B. bassiana . Intron retention was the most abundant type of AS, accounting for 87.1% of all splicing events and exon skipping events were rare, only accounting for 2.0% of all events. Functional distribution analysis indicated an association between alternatively spliced genes and several physiological processes. Notably, B. bassiana autophagy‐related gene 8 ( BbATG8 ), an indispensable gene for autophagy, was spliced at an alternative 5′ splice site to generate two transcripts ( BbATG8‐α and BbATG8‐β ). The BbATG8‐α transcript was necessary for fungal autophagy and oxidation tolerance, while the BbATG8‐β transcript was not. These two transcripts differentially contributed to the formation of conidia or blastospores as well as fungal virulence. Thus, AS acts as a powerful post‐transcriptional regulatory strategy in insect mycopathogens and significantly mediates fungal transcriptional adaption to host niches.

MiR-340 Regulates Fibrinolysis and Axon Regrowth Following Sciatic Nerve Injury - Shiying Li; Ruirui Zhang; Ying Yuan; Sheng Yi; Qianqian Chen; Leilei Gong; Jie Liu; Fei Ding; Zheng Cao; Xiaosong Gu (Molecular Neurobiology, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

Seasonal variation of pheophorbide a and flavonoid in different organs of two Carpinus species and its correlation with immunosuppressive activity - Qianqian Sheng; Xianying Fang; Zunling Zhu; Wei Xiao; Zhenzhong Wang; Gang Ding; Linguo Zhao; Yujian Li; Ping Yu; Zhibin Ding; Qinru Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Aeromagnetic data and geological structure of continental China: A review - Sheng-Qing Xiong; Jing Tong; Yan-Yun Ding; Zhan-Kui Li (Applied Geophysics, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Sorption and degradation of selected organic UV filters (BM-DBM, 4-MBC, and OD-PABA) in laboratory water-sediment systems - Sheng Li; Guanghua Lu; Zhengxin Xie; Jiannan Ding; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Study of the genomic constitution of the German mirror carp - Ya-Juan Li; Bo Liu; He Zhou; Yang-Chun Gao; Min Gao; Yu-Sheng Wang; Ding-Chen Cao; Xiao-Wen Sun (Aquaculture International, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

A simple method for construction of artificial microRNA vector in plant - Yang Li; Yang Li; Sunping Zhao; Sheng Zhong; Zhaohai Wang; Bo Ding; Yangsheng Li (Biotechnology Letters, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Human umbilical cord-derived MSC culture: the replacement of animal sera with human cord blood plasma - Yan Ding; Hua Yang; Jing Bo Feng; Ying Qiu; Dong Sheng Li; Yi Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Potential hepatotoxicity of geniposide, the major iridoid glycoside in dried ripe fruits of Gardenia jasminoides (Zhi-zi) - Yue Ding; Tong Zhang; Jian-sheng Tao; Li-ying Zhang; Jian-rong Shi; Guang Ji (Natural Product Research, 2013)

Meta-analysis of the effect of KCNQ1 gene polymorphism on the risk of type 2 diabetes - Jun Liu; Fang Wang; Yueyue Wu; Xinmei Huang; Li Sheng; Jiong Xu; Bingbing Zha; Heyuan Ding; Zaoping Chen; Tiange Sun (Molecular Biology Reports, 2013)

Effect of the P450 oxidoreductase *28 polymorphism on the pharmacokinetics of tacrolimus in Chinese healthy male volunteers - Jing-Jing Zhang; Hua Zhang; Xiao-Liang Ding; Sheng Ma; Li-Yan Miao (European Journal of Clinical Pharmacology, 2013)

Curcumin Ameliorates the Neurodegenerative Pathology in A53T α-synuclein Cell Model of Parkinson’s Disease Through the Downregulation of mTOR/p70S6K Signaling and the Recovery of Macroautophagy - Tian-Fang Jiang; Ying-Jie Zhang; Hai-Yan Zhou; Hong-Mei Wang; Li-Peng Tian; Jun Liu; Jian-Qing Ding; Sheng-Di Chen (Journal of Neuroimmune Pharmacology, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Erratum to: Comparative codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Lmx1b can promote the differentiation of embryonic stem cells to dopaminergic neurons associated with Parkinson’s disease - Li-Peng Tian; Shi Zhang; Ying-Jie Zhang; Jian-Qing Ding; Sheng-Di Chen (Biotechnology Letters, 2012)

Comparative the codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Larval settlement and metamorphosis of the mussel Mytilus coruscus in response to natural biofilms - Chong Wang; Wei-Yang Bao; Zhong-Qi Gu; Yi-Feng Li; Xiao Liang; Yun Ling; Sheng-Li Cai; He-Ding Shen; Jin-Long Yang (Biofouling, 2012)

Saline conducted electric coagulation (SCEC): original experience in experimental hepatectomy - Guo-ping Ding; Li-ping Cao; Da-ren Liu; Ri-sheng Que (Journal of Zhejiang University-SCIENCE B, 2012)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

Mercury Biomagnification in the Aquaculture Pond Ecosystem in the Pearl River Delta - Zhang Cheng; Peng Liang; Ding-Ding Shao; Sheng-Chun Wu; Xiang-Ping Nie; Kun-Ci Chen; Kai-Bin Li; Ming-Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

USEtox human exposure and toxicity factors for comparative assessment of toxic emissions in life cycle analysis: sensitivity to key chemical properties - Ralph K. Rosenbaum; Mark A. J. Huijbregts; Andrew D. Henderson; Manuele Margni; Thomas E. McKone; Dik van de Meent; Michael Z. Hauschild; Shanna Shaked; Ding Sheng Li; Lois S. Gold; Olivier Jolliet (The International Journal of Life Cycle Assessment, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Analysis of codon usage in Newcastle disease virus - Meng Wang; Yong-sheng Liu; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yuan-xing Gu; Jie Zhang (Virus Genes, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

Characterization of a wheat HSP70 gene and its expression in response to stripe rust infection and abiotic stresses - Ying-Hui Duan; Jun Guo; Ke Ding; Shu-Juan Wang; Hong Zhang; Xi-Wei Dai; Yue-Ying Chen; Francine Govers; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2011)

Analysis of codon usage in bovine viral diarrhea virus - Meng Wang; Jie Zhang; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yong-sheng Liu (Archives of Virology, 2011)

Developing new SSR markers from ESTs of pea (Pisum sativum L.) - Ya-ming Gong; Sheng-chun Xu; Wei-hua Mao; Qi-zan Hu; Gu-wen Zhang; Ju Ding; Ya-dan Li (Journal of Zhejiang University-SCIENCE B, 2010)

Improvement of heart function in postinfarct heart failure swine models after hepatocyte growth factor gene transfer: comparison of low-, medium- and high-dose groups - Zhi-jian Yang; Bo Chen; Zhang Sheng; Ding-guo Zhang; En-zhi Jia; Wei Wang; Dong-chao Ma; Tie-bing Zhu; Lian-sheng Wang; Chun-jian Li; Hui Wang; Ke-jiang Cao; et al. (Molecular Biology Reports, 2010)

Extensive population expansion of Pedicularis longiflora (Orobanchaceae) on the Qinghai‐Tibetan Plateau and its correlation with the Quaternary climate change - FU‐SHENG YANG; YU‐FEI LI; XIN DING; XIAO‐QUAN WANG (Molecular Ecology, 2008)
The Qinghai‐Tibetan Plateau (QTP) is thought to be more strongly affected by the Quaternary glaciations than most other regions of the same latitude. It would be of great interest to investigate the population genetic structure of organisms distributed on the platform and its correlation with the Quaternary climatic oscillations. Here we used the chloroplast (cp)DNA trn T‐ trn F sequence to study genetic variation and phylogeography of Pedicularis longiflora , an alpine herb with extensive distribution on the QTP. Based on a range‐wide sampling comprising 41 populations and 910 individuals, we detected 30 cpDNA haplotypes that were divided into five clades by phylogenetic and network analyses and a strong phylogeographical structure. All haplotypes but one in the three basal clades occur exclusively in the southeast QTP, whereas haplotypes in the young clade V occupy almost the whole species range. In particular, the young haplotype H18 occurs in 420 individuals, even at a frequency of 100% in some QTP platform populations and the Altai population. The haplotype distribution pattern, together with molecular clock estimation and mismatch distribution analysis, suggests that the southeast QTP was either a refuge for P . longiflora during the Quaternary climatic change or is the place of origin of the species. The present wide distribution of the species on the QTP platform has resulted from recent population expansions which could be dated back to 120 000–17 000 years ago, a period mostly before the last glacial maximum. The possible relationships among geographic genetic structure, climatic change and species diversification in Pedicularis are also discussed.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Rapid discrimination of H5 and H9 subtypes of avian influenza viruses and Newcastle disease virus by multiplex RT-PCR - Hao-tai Chen; Jie Zhang; De-hui Sun; Ji-le Zhang; Xue-peng Cai; Xiang-tao Liu; Yao-zhong Ding; Li-na Ma; Sheng-hai Yang; Lei Jin; Yongsheng Liu (Veterinary Research Communications, 2008)

Identification of QTL for maize resistance to common smut by using recombinant inbred lines developed from the Chinese hybrid Yuyu22 - Jun-qiang Ding; Xiao-ming Wang; Subhash Chander; Jian-sheng Li (Journal of Applied Genetics, 2008)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

The distribution and economic losses of alien species invasion to China - Haigen Xu; Hui Ding; Mingyan Li; Sheng Qiang; Jianying Guo; Zhengmin Han; Zongguo Huang; Hongying Sun; Shunping He; Hairong Wu; Fanghao Wan (Biological Invasions, 2006)

A new dihydroisocoumarin from the rhizomes of Notopterygium forbesii - Yan-Hui Li; Fan Luo; Shu-Lin Peng; Jian Liang; Li-Sheng Ding (Natural Product Research, 2006)

Sensory exotropia subsequent to senile cataract - Ding-hua Lou; Ye-sheng Xu; Yu-min Li (Journal of Zhejiang University-SCIENCE B, 2005)

A genetic diversity comparison between captive individuals and wild individuals of Elliot’s Pheasant (Syrmaticus ellioti) using mitochondrial DNA - Ping-ping Jiang; Qiu-lei Lang; Sheng-guo Fang; Ping Ding; Li-ming Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Forest landscape pattern dynamics of Luoning County in Henan Province and its driving forces - Sheng-yan Ding; Le-xiang Qian; Xin-xiang Cao; Shuang Li; Hao-min Li (Chinese Geographical Science, 2003)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)